Mobile resistance determinants, plasmid replicon types and phylogeny among Escherichia coli strains isolated from cats and dogs: Epidemiological typing of E.coli - Kalaycı Yüksek, F; Gümüş, D; Macunluoğlu, AC; Eroğlu, E; Camadan, D; Anğ Küçüker, M (Journal of the Hellenic Veterinary Medical Society, 2023)
Abstract Multidrug resistance is a great challenge for the treatment of infectious diseases. We determined antibiotic resistance patterns, integrons, plasmid-mediated ESBL-, AmpC beta-lactamase-, carbapenemase-, colistin resistance genes, plasmid replicon types and phylogeny of fecal E. coli strains isolated from domestic cats and dogs in Turkey. A total of 104 fecal samples of healthy 49 cats and 55 dogs were examined. The integrons, plasmid-mediated resistance genes, plasmid replicon types and phylogroups were determined by PCR. Antimicrobial susceptibilities were performed by disc diffusion and microdilution methods. coli strains were mostly resistant to AMP (56.73%), SXT (39.42%), CTX (38.46%) and CIP (30.77%). Colistin resistance was not detected. ESBL and carbapenemase rates were 35.5 % and 7.69%, respectively. Eighty (76.9%) and 49 (47.1%) strains were harboring class I and class II integrons, respectively. Besides 12 strains were shown to possess class III integrons. The most frequently detected genes were blaCTX-M (48.08%), blaTEM (45.19%) and blaVIM (20.19%). In our study, none of strains were positive for mcr-1 and mcr-2 genes. Integrons were mostly found on plasmids of incompatibility groups IncF (71.25%) and strains bearing CTX-M and TEM carried a wide range of plasmid replicons of which IncF, IncFIB, IncK, and IncN. The majority of the strains were grouped in B2 (31.73%) and B1 (22.12%) and resistant bacteria mostly belonged to phylogroup B2. We showed an increasing trend in ESBL-producing E. coli among fecal microbiota members. E. coli strains with different plasmid replicon types and phylogroups isolated from cats and dogs can be resistant to various antibiotics which are used in human and veterinary medicine.